The coupling relationship between tourism economy and air quality in China: A province-level analysis - Zhao, Shuhong; Li, Qin; Kong, Yingying; Chen, Xi (Frontiers in Environmental Science, 2023)
The development of tourism economy depends on air quality to a large extent, and good air quality is conducive to promoting the development of tourism economy. And it is crucial to understand the coupled and coordinated relationship between them. In this study, an index system was constructed to evaluate the development status of tourism economy and air quality system, and the entropy value method was used to weight the indexes. Using panel data of Chinese provinces from 2014 to 2020, a coupled coordination model was established, focusing on the degree of coordination between tourism economy and air quality. The empirical results show that during the sample period, China's tourism economic index is decreasing, and the regional development is unbalanced, showing the gradient of eastern region > central region > western region. The air quality index, on the other hand, fluctuates and increases, showing a spatial distribution pattern of "weekly high, high and low" of western region > eastern region > central region. The coupling coordination level of both regions shows an increasing trend, with the eastern region having the highest coupling coordination level and always in the basic coordination stage; the central region has the second highest coupling coordination level and the coupling coordination level is steadily increasing; the western region has the worst coupling coordination level and the coupling system tends to decline. The main type of coupling coordination effect is tourism economy lagging type, and the overall performance shows that the ambient air quality condition is better than the tourism economy development. This study clearly reveals the evolution, degree and types of coupling coordination in the tourism economy and air quality of the two systems, which contributes to the understanding of coupling and synergy of industrial development and ecological environment.